Peran Majlis Ta’lim Al- Muhsinin dalam Meningkatkan Pemahaman Keagamaan Masyarakat di Dusun Selak Ampan Desa Pijot: The Role of Majlis Ta'lim Al-Muhsinin in Increasing Community Religious Understanding in Selak Ampan Hamlet, Pijot Village - Lalu Muh. Fahri; Nasri; Indra Wijaya (Pendidikan Al-Gafari, 2026)
The main objective of establishing a religious study group is to spread Islamic da'wah and save the community from adversity, where the Islamic study group has developed rapidly in Indonesia. This study aims to determine the role of the Al-Muhsinin Islamic Study Group in improving the religious understanding of the community in Selak Ampan Hamlet, Pijot Village. The background of this study is the low level of religious understanding in the community, even though the majority are Muslim. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The research subjects consisted of the administrators of the Islamic Study Group and the community who actively participated in the activities. The results show that the Al-Muhsinin Islamic Study Group has a strategic role in fostering faith, increasing Islamic understanding, and strengthening Islamic brotherhood. Routine activities such as religious studies, lectures, and religious discussions have a positive impact on the community's religious awareness. Supporting factors for the success of this activity include community enthusiasm, the role of religious leaders, and the availability of worship facilities. The inhibiting factors are limited time, community busyness, and lack of cadre development.